Unravelling the anti-inflammatory activity of Cyperus rotundus essential oil through gas chromatography-mass spectrometry analysis, network pharmacology, and molecular docking approaches - Mohanty, S; Ray, A; Mohanty, M; Panda , P C; Nayak , S; Sahoo, A; Rani, K S (Plant Science Today, 2025)
Cyperus rotundus rhizome is used in the traditional system of medicine to treat various diseases. The rhizomes of this plant are traditionally used as medicine for treatments of stomach pain, bowel disorders, and inflammatory pain. The present study aims to characterize the chemical constituents of the C. rotundus rhizomes essential oil (CREO) and to evaluate its possible mechanism of action as an anti-inflammatory agent by an integrative approach of gas chromatography-mass spectrometry (GC-MS), network pharmacology, and molecular docking analysis. The compound-target-disease network revealed cubenol, gamma murolene, cyperotundone, delta selinene, alpha copaene, alpha pinene, and beta caryophyllene are core compounds with higher degree values. Protein-protein interaction analysis revealed IL1B, IL10, IL6, PTGS2, TNF, and STAT3 as hub targets. A total of 1000 biological processes, 142 cellular components, and 241 molecular functional pathways were enriched. Molecular docking analysis revealed that hub compounds and protein targets had strong binding affinity between them. The top two docked poses with the lowest binding energy were identified as PTGS2-Cubenol and IL10-Gamma murolene with binding energies of -7.9 and -7.2 kcal/mol, respectively. A molecular dynamics study revealed that the PTGS2-Cubenol and IL10-Gamma murolene complex had a good amount of deformability. These results demonstrated that CREO can act on numerous proteins and pathways to form a systematic pharmacological network, and they can be considered as a candidate drug for treating inflammatory-related disorders